Electrochemical Characteristics of Austenitic Stainless Steel in Mixed Chloride – Molybdate Solutions - Zatkalikova, Viera; Markovicova, Lenka; Wrobel-Knysak, Anna (Communications - Scientific letters of the University of Zilina, 2017)
The effect of molybdate addition to chloride solutions on resistance of AISI 316Ti stainless steel to pitting corrosion was studied. Potentiodynamic polarization tests were performed in 1 M and 0.1 M chloride acidified solutions with various additions of sodium molybdate at room temperature. The presented results compare the effect of molybdate anions on quality of passive film (expressed by the pitting potential) in both chloride solutions. The pitting potential increases with the increase of inhibitor concentration. The inhibitive effect of molybdate ions is stronger in chloride solution of lower aggressiveness (0.1M).